Ireland : Financial Sector Assessment Program: Technical Note-Banking Supervision and Update on the Assessment of Observance of the Basel Core Principles. (IMF Staff Country Reports; Country Report, 2016)
This Technical Note discusses the findings and recommendations made in the Financial Sector Assessment Program for Ireland in the areas of banking supervision and observance of the Basel core principles. The effective operational implementation of the Single Supervisory Mechanism (SSM) is well established in Ireland, and all authorities are actively engaged and committed to the new supervisory framework led by the European Central Bank. The SSM has further strengthened the prudential regulation and supervision of banks since the time of the 2013 assessment. The transition to the operational implementation of the SSM has not resulted in major gaps in banking supervision, but some transitional challenges remain.